2021
DOI: 10.3389/fimmu.2021.626493
|View full text |Cite
|
Sign up to set email alerts
|

Mitf Involved in Innate Immunity by Activating Tyrosinase-Mediated Melanin Synthesis in Pteria penguin

Abstract: The microphthalmia-associated transcription factor (MITF) is an important transcription factor that plays a key role in melanogenesis, cell proliferation, survival and immune defense in vertebrate. However, its function and function mechanism in bivalve are still rarely known. In this research, first, a Mitf gene was characterized from Pteria penguin (P. penguin). The PpMitf contained an open reading frame of 1,350 bp, encoding a peptide of 449 deduced amino acids with a highly conserved basic helix-loop-helix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…From there, eight of them were uniquely expressed among the innate professional phagocytes (Figure 5h , dash box), functioning as an interlinked regulatory network (Figure 5i ). While most of them revealed upregulated trends in Hainan LLIs, expression levels the microphthalmia‐associated transcription factor ( MITF ) which robustly regulate genes in the innate immune signaling pathways (Yu et al, 2021 ); the Kruppel‐like factor‐4 ( KLF4 ) that governs monocyte differentiation (Feinberg et al, 2007 ); and the activating transcription factor‐3 ( ATF3 ) that promotes macrophage migration and M2 polarization via suppressing the M1‐like fate (Sha et al, 2017 ) were only ones significantly induced (Figure 5j , Figure S12 ). Notably, these transcription factors were also direct targets of nuclear INSR, where robust binding sites were identified at their core promoter regions (Figure 5k ).…”
Section: Resultsmentioning
confidence: 99%
“…From there, eight of them were uniquely expressed among the innate professional phagocytes (Figure 5h , dash box), functioning as an interlinked regulatory network (Figure 5i ). While most of them revealed upregulated trends in Hainan LLIs, expression levels the microphthalmia‐associated transcription factor ( MITF ) which robustly regulate genes in the innate immune signaling pathways (Yu et al, 2021 ); the Kruppel‐like factor‐4 ( KLF4 ) that governs monocyte differentiation (Feinberg et al, 2007 ); and the activating transcription factor‐3 ( ATF3 ) that promotes macrophage migration and M2 polarization via suppressing the M1‐like fate (Sha et al, 2017 ) were only ones significantly induced (Figure 5j , Figure S12 ). Notably, these transcription factors were also direct targets of nuclear INSR, where robust binding sites were identified at their core promoter regions (Figure 5k ).…”
Section: Resultsmentioning
confidence: 99%
“…Tyrosinase plays a critical role in the synthesis of eumelanin, the most photoprotective black-brown melanin [ 34 ]. MITF protein plays a pivotal role in melanocyte lineage development and serves as a key transcription factor regulating the expression of tyrosinase and TYRP1 genes [ 18 ]. However, direct involvement of MITF in regulating melanin synthesis or the expression of endogenous tyrosinase or TYRP1 remains unproven.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed the expression of mRNA related to melanin production in B16F10 cells after co-incubation with exosomes and found that the exosomes promote melanin production by increasing tyrosinase-related protein 1 (TYRP1) expression and decreasing microphthalmia-associated transcription factor (MITF) expression in the cells. Our finding is of particular interest since MITF is known to upregulate the expression of proteins involved in melanin synthesis, such as tyrosinase and TYRP1 [ 18 ]. We also conducted miRNA profiling of the exosomes and found the expression of many melanogenesis-related genes in the exosomes isolated from B16F10 cells.…”
Section: Introductionmentioning
confidence: 99%
“…The protein-DNA–binding specificity is provided by the basic region in protein and the key DNA interacting bases along with the flanking region. Most of the MITF-bound sites are CAGGTG “E-box” motifs flanked by A and/or T. This consensus “E-box” sequence is located in the promoter region of the MITF target genes like BCL2, tyrosinase, and cathepsin K (CTSK) ( 35 , 36 ). Interestingly, the genes involved in pigmentation have a specific “E-box” variant with a flanking T at the 5′ end of the core “E-box” motif.…”
Section: Discussionmentioning
confidence: 99%